Precalculus the easy way - Leff, Lawrence S.; Pawlowski, Christina M. (Easy way., 2019)
"A series of easy-to-follow lessons are designed for self-teaching and rapid learning to help students learn precalculus the easy way. Barron's Precalculus: The Easy Way features a generous number of step-by-step demonstration examples as well as numerous tables, graphs, and graphing-calculator-based approaches." --Amazon.com.